2015
DOI: 10.1097/ppo.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Evaluation of Sentinel Nodes

Abstract: Optimal utilization of sentinel node biopsy in the care of cancer patients requires cooperation between the radiologist, surgeon, and the pathologist. Accurate pathologic diagnosis of the sentinel node is central to correct staging, optimal treatment decisions, and precise prognostication of patients with melanoma, breast, colorectal, lung, and gastric cancer. Intraoperative handling, gross dissection, and histologic/immunohistochemical evaluation techniques are all key components of this process. Although not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Deeper, parenchymal location worsened survival [ 35 ]. In some types of cancer, including breast cancer, nodal tumor deposits below 0.2 mm are considered N0 [ 36 ]. According to the AJCC melanoma database, the long-term survival rate of patients with SN metastases <0.2 mm was excellent (96%) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deeper, parenchymal location worsened survival [ 35 ]. In some types of cancer, including breast cancer, nodal tumor deposits below 0.2 mm are considered N0 [ 36 ]. According to the AJCC melanoma database, the long-term survival rate of patients with SN metastases <0.2 mm was excellent (96%) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that detecting metastasis from ILC intraoperatively can be challenging . This is attributed to the presence of metastasis usually as single cells instead of the glandular clusters seen in case of ductal carcinoma, to the morphological similarity of lobular carcinoma cells to normal lymph node elements, and also to the more common subcapsular location of metastatic deposits in the SLN (Figure A,B) .…”
Section: Discussionmentioning
confidence: 99%
“…Frozen section (FS) and intraoperative imprint cytology (IC; touch‐preparations) are two methods used to evaluate SLN, with intraoperative IC being the preferred method because of its rapid turnaround time (TAT) and tissue preservation . However, cytologic evaluation in cases of invasive lobular carcinoma (ILC) can be challenging, with a reported higher rate of false‐negative results when compared to cases of ductal carcinoma . At our institution, intraoperative evaluation of SLNs of patients with breast carcinoma is performed using IC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los ganglios pequeños (de menos de 4 mm de diámetro), generalmente se envían en su totalidad, y los más grandes se seccionan en serie a intervalos de 2-3 mm a lo largo de su eje más largo, se incrustan en parafina y se tiñen con Hematoxilina y Eosina (H&E) y otros métodos de tinción (69,70). Las metástasis de los ganglios linfáticos se pueden dividir en macrometástasis (depósitos tumorales de más de 2 mm de diámetro), micrometástasis (depósitos tumorales de 0,2-2 mm de diámetro) y células tumorales aisladas (células individuales o grupos aislados de células con un diámetro máximo de 0,2 mm o menos de 200 células en una sola sección histológica) (71).…”
Section: Trazadores Utilizados Para La Biopsia De Ganglio Centinela E...unclassified